Overinterpretation and Overtreatment of Low-Titer Antibodies Against Contactin-Associated Protein-2 - Bien, Christian G. (Frontiers in Immunology, 2018)
Antibodies (abs) against neural or glial antigens have become important diagnostic markers of autoimmune encephalitides. A key requirement for interpretation of any test in clinical medicine is specificity. In this work, a 35-year-old female patient with low-titer contactin-associated protein-2 abs not satisfying clinical criteria of autoimmune encephalitis is reported. The patient had a recurrent depressive disorder and, at the time of the ab study, a moderate depressive episode. Overinterpretation and misinterpretation of patient’s complaints and paraclinical study results fueled the idea of an autoimmune encephalitis. It is suggested to check patients with supposedly positive ab test results critically for clinical criteria, titer cutoffs, and ab-typical epidemiological features like age and sex.